1974
DOI: 10.2134/agronj1974.00021962006600020017x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Sugar Content in Seed of Glycine max (L.) Merrill and G. soja Sieb. and Zucc.1

Abstract: The flatus‐producing factor in soybean [Glycine max (L.) Merrill] seed appears to be associated with the sugars raffinose and stachyose. The objective of this investigation was to measure the variability of total sugar and individual sugars in seed from soybean cultivars, the soybean genetic type collection, plant introductions of G. max that were formerly known as G. gracilis Skvortz., and plant introductions of G. soja Sieb. and Zucc. Among the cultivars, ‘Bansei’ had the highest total sugar, sucrose, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
72
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 2 publications
16
72
4
Order By: Relevance
“…Soybean seed contain about 42% protein and 19.5% oil [1], 33% carbohydrates [2][3][4], and from 1161 to 3309 µg·g −1 isoflavones [4,5]. Soybean seed contain five main fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean seed contain about 42% protein and 19.5% oil [1], 33% carbohydrates [2][3][4], and from 1161 to 3309 µg·g −1 isoflavones [4,5]. Soybean seed contain five main fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean seed contain five main fatty acids. Two are saturated fatty acids (palmitic, C16:0, ranging from 10% to 12%; stearic, C18:0, ranging from 2.2% to 7.2%), and three are unsaturated fatty acids (oleic, C18:1, about 24%; linoleic, C18:2, about 54%; linolenic, C18:3, about 8.0%) [2,6,7]. High oleic acid and low linoleic and linolenic acids are desirable because they contribute to oil stability.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean seeds contain about 42% protein and 19.5% of oil [1], 33% carbohydrates [2,3], and essential minerals [4]. Soybean seeds contain saturated fatty acids, including palmitic acid (C16:0) (10% to 12%) and stearic acid (C18:0) (2.2% to 7.2%), and unsaturated fatty acids, including oleic acid (C18:1) (24%), linoleic acid (C18:2) (54%), and linolenic acid (C18:3) (8.0%) [2,5]. One of the benefits of soybean seed is that it contains secondary natural metabolite compounds, including phenolic acid, lignin, and isoflavones.…”
Section: Introductionmentioning
confidence: 99%
“…Greater and Fehr (2000) reported that the mean total sugar content of 23 soybean cultivars grown at 8 Iowa locations in 1998 ranged from 19 to 21.4% on DM basis. The average total sugar contents were 10.6, 7.5 and 5.9%, respectively, in the seeds of G. max, G. gracilis and G. soja (Hymowitz and Collins, 1974). The seeds of G. max had a higher total sugar content, with the highest value being 16.6%.…”
Section: Carbohydrates In Soybeanmentioning
confidence: 93%